Antibiogram of Vibrio parahaemolyticus Isolated from Fish and Prawn in and around Navsari, Gujarat - Shirisha, Arrabelli; Savalia, Chandubhai V; Kalyani, Irsadullahkhan H; Kumar, Niranjan; Makwana, Pushpa M; Kumar, Rajeev (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Food-borne Vibrio parahaemolyticus has global economic and public health concern. The frequent way for humans to contract these bacteria is through seafood. In this study, 350 samples were analysed for the presence of Vibrio parahaemolyticus. Of those, 40 samples were found positive for the bacteria. Ten different antibiotics were used to test the antibiotic sensitivity of these 40 isolates, and they exhibited variable susceptibility pattern. The isolates showed 100% resistance to penicillin G followed by 80% and 75% resistance to ampicillin and streptomycin, respectively. The isolates were highly sensitive to ciprofloxacin (97.5%), followed by trimethoprim (90%), gentamicin (90%), chloramphenicol (87.5%), amikacin (80%), tetracycline (65%) and cephalothin (65%). Of the 40 isolates, 45.0%, 22.5%, 5.0%, 7.5% isolates were found resistant to 3, 4, 5 and 6 antibiotics, respectively. Multiple antibiotic resistance (MAR) index value above 0.2 was shown by 80% of the isolates. The presence of MAR highlights the essential need to determine drug susceptibility and monitor antimicrobial resistance profiles. This is crucial for enhancing food safety and protecting public health. By identifying resistant strains, we can develop more effective treatment strategies and implement measures to control the spread of resistant pathogens, thus preserving antibiotic efficacy and ensuring public well-being